Accounting and finance : an introduction - McLaney, E. J.; Atrill, Peter (Harlow : United Kingdom, 2020)
"We recognise that most readers will not have studied accounting or finance before, and we have therefore tried to write in a concise and accessible style, minimising the use of technical jargon. We have also tried to introduce topics gradually, explaining everything as we go. Where technical terminology is unavoidable we try to provide clear explanations"--
Revised edition of the authors' Accounting and finance, [2018]
Includes bibliographical references and index.
Keywords: Accounting